Flow Boiling in Microgap Channels Experiment, Visualization and Analysis - Alam, Tamanna; Lee, Poh Seng; Jin, Liwen (SpringerBriefs in Thermal Engineering and Applied Science,, 2014)
Flow Boiling in Microgap Channels: Experiment, Visualization and Analysis presents an up-to-date summary of the details of the confined to unconfined flow boiling transition criteria, flow boiling heat transfer and pressure drop characteristics, instability characteristics, two phase flow pattern and flow regime map and the parametric study of microgap dimension. Advantages of flow boiling in microgaps over microchannels are also highlighted. The objective of this Brief is to obtain a better fundamental understanding of the flow boiling processes, compare the performance between microgap and conventional microchannel heat sinks, and evaluate the microgap heat sink for instabilities and hotspot mitigation.